Tat-fimbriae (“tafi”): An unusual type of haloarchaeal surface structure depending on the twin-arginine translocation pathway - Anna V. Galeva; Dahe Zhao; Alexey S. Syutkin; Marina Yu Topilina; Sergei Yu Shchyogolev; Elena Yu Pavlova; Olga M. Selivanova; Igor I. Kireev; Alexey K. Surin; Gennady L. Burygin; Jingfang Liu; Hua Xiang; et al. (iScience)
Summary: The surface structures of archaeal cells, many of which exist at high temperatures, high salinity, and non-physiological pH, are key factors for their adaptation to extreme living conditions. In the haloarchaeon Haloarcula hispanica, we have discovered a thin filamentous surface appendage called tat-fimbriae (''tafi''), which were identified to be composed of three protein subunits, TafA, TafC, and TafE, among which TafA is the major fimbrial subunit. Molecular genetic evidence demonstrates TafA was transported through the twin-arginine translocation pathway (Tat-pathway). Based on protein structure prediction (including AlphaFold 3), tafi exhibits a linear structure: TafC at the tip, TafE acting as an adapter, TafA forming the core filament, and they link the fourth subunit TafF, anchoring tafi to the cell wall. To our knowledge, this is the first case that the Tat-pathway has been linked to the secretion of protein subunits forming prokaryotic filamentous structures.